The effect of a water dam on Lake Powidzkie and its vicinity - Nowak, Bogumił Michał; Ptak, Mariusz (Bulletin of Geography. Physical Geography Series, 2018)
The paper presents an attempt of assessment of the effect of damming of lakes on water resources based on the example of Lake Powidzkie (Central Poland) and its catchment. The analysed object is located in a region with the greatest water deficits in Poland. A co-occurrence of unfavourable natural and anthropogenic factors contributed to a considerable reduction of water resources retained in the discussed lake. Particularly low water levels were recorded in the 1990’s and in the first decade of the 21st century. The situation was not improved by a water dam constructed on the outflow from the lake in the 1960’s, among others due to neglect in its exploitation. Owing to the modernisation of the dam in 2010 and favourable hydrological situation in winter 2011, it was possible to retain excess water and substantially reduce its outflow. The restoration of the lost water resources, and hydrological benefits resulting from the fact were still observed several years later. Problems related to water deficits are becoming increasingly common in many regions of the world. A solution mitigating such a situation can be among others damming natural lakes. It is simpler, cheaper, and less invasive for the environment than the construction of new water reservoirs.